Shared competence forms the basis of gill arch and paired fin serial homology - Michael T. C. Wen; Victoria E. Prince; J. Andrew Gillis (Proceedings of the National Academy of Sciences, 2026)
The origin of paired fins is an unresolved controversy in vertebrate evolutionary biology. Karl Gegenbaur famously proposed that paired fins evolved by the transformation of a gill arch, but this hypothesis remains largely unsupported by the fossil record. Also, seemingly at odds with gill arch-paired fin serial homology are their distinct embryonic origins from neural crest and lateral plate mesoderm, respectively. We have previously shown that skate gill arch skeletal elements may derive solely from neural crest, or from a mixture of neural crest and mesoderm, and we have shown that skate gill arches and jawed vertebrate fins/limbs share several molecular patterning mechanisms. Here, we show in the little skate ( Leucoraja erinacea ) that neural crest and lateral plate mesoderm-derived mesenchyme are developmentally equivalent and interchangeable in the pharyngeal arches and fin buds. Using heterotopic transplantation experiments, we find that neural crest cells can contribute to the typically mesoderm-derived fin skeleton, and that lateral plate mesodermal mesenchyme can contribute to the typically neural crest-derived jaw skeleton. These findings point to shared skeletogenic competence of neural crest and mesoderm-derived mesenchyme at the head–trunk interface. We argue that this shared competence accounts for the anatomical and developmental parallels of the gill arch and paired fin/limb skeletons and forms the basis of their serial homology.